Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1161/strokeaha.120.032402
|View full text |Cite
|
Sign up to set email alerts
|

Unique Subtype of Microglia in Degenerative Thalamus After Cortical Stroke

Abstract: Background and Purpose: Stroke disrupts neuronal functions in both local and remotely connected regions, leading to network-wide deficits that can hinder recovery. The thalamus is particularly affected, with progressive development of neurodegeneration accompanied by inflammatory responses. However, the complexity of the involved inflammatory responses is poorly understood. Herein we investigated the spatiotemporal changes in the secondary degenerative thalamus after cortical stroke, using targeted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 34 publications
4
37
0
Order By: Relevance
“…Notably, the impairment of microglial function correlated with Aβ plaque deposition, both temporally and spatially, suggesting that with further studies into the later stages of SND a relationship between non-responsive microglia and Aβ plaques may be observed [ 213 ] This is particularly detrimental given the fact that Aβ deposition plays a key role in the development of dementia [ 214 ]. In support of this, a recent study identified a unique subtype of CD11c-positive microglia in the thalamus 28 days following MCAo in mice [ 207 ]. Using flow cytometry, the group was able to indicate molecular signatures in the post-stroke microglia that are similar to neurodegenerative disease-associated microglia [ 207 ].…”
Section: Neuroinflammation In Sndmentioning
confidence: 69%
See 1 more Smart Citation
“…Notably, the impairment of microglial function correlated with Aβ plaque deposition, both temporally and spatially, suggesting that with further studies into the later stages of SND a relationship between non-responsive microglia and Aβ plaques may be observed [ 213 ] This is particularly detrimental given the fact that Aβ deposition plays a key role in the development of dementia [ 214 ]. In support of this, a recent study identified a unique subtype of CD11c-positive microglia in the thalamus 28 days following MCAo in mice [ 207 ]. Using flow cytometry, the group was able to indicate molecular signatures in the post-stroke microglia that are similar to neurodegenerative disease-associated microglia [ 207 ].…”
Section: Neuroinflammation In Sndmentioning
confidence: 69%
“…In support of this, a recent study identified a unique subtype of CD11c-positive microglia in the thalamus 28 days following MCAo in mice [ 207 ]. Using flow cytometry, the group was able to indicate molecular signatures in the post-stroke microglia that are similar to neurodegenerative disease-associated microglia [ 207 ].…”
Section: Neuroinflammation In Sndmentioning
confidence: 69%
“…These findings should of course be independently reproduced by another laboratory like our findings in young male rats recently were, 38 but could suggest a bigger contribution of Kv1.3 high microglia and T cells to stroke pathophysiology in aged animals. CD11c + microglia, which express high levels of Kv1.3, 16 have recently been described to drive secondary, neurodegenerative changes in the thalamus after cortical strokes 39 . Regarding T cells, old C57BL/6 mice of both sexes recruit significantly more T cells into the brain than young and middle‐aged mice following 60‐min tMCAO 31 and CD4 T‐cell depletion has been shown to improve behavioral outcomes on day‐7 post‐MCAO in aged mice without reducing infarct size 40 .…”
Section: Discussionmentioning
confidence: 99%
“…CD11c + microglia, which express high levels of Kv1.3, 16 have recently been described to drive secondary, neurodegenerative changes in the thalamus after cortical strokes. 39 Regarding T cells, old C57BL/6 mice of both sexes recruit significantly more T cells into the brain than young and middle‐aged mice following 60‐min tMCAO 31 and CD4 T‐cell depletion has been shown to improve behavioral outcomes on day‐7 post‐MCAO in aged mice without reducing infarct size. 40 There are further reports that brain‐resident memory CD8 T cells, which appear to regulate microglia homeostasis under normal conditions, potentiate inflammation following ischemic injury by producing inflammatory cytokines and driving cytotoxic responses.…”
Section: Discussionmentioning
confidence: 99%
“…These subpopulations were barely detected in vehicle-treated SWI samples but were substantially represented in the AMX treated mice. TMEM119 + CD11c + microglia (which may encompass more than one subset) has been recently identified as DAM, a subpopulation characteristically associated with neurodegenerative diseases ( Keren-Shaul et al, 2017 ; Krasemann et al, 2017 ; Cao et al, 2021 ) and white matter aging ( Sato-Hashimoto et al, 2019 ; Safaiyan et al, 2021 ). Expression profiling of DAM has revealed the upregulation of genes involved in lipid metabolism (most notably, ApoE) and apparently reduced capacity for engulfment, phagocytosis and degradation ( Krasemann et al, 2017 ; Ulland et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%